Union of South Africa. House of Assembly. Debates of the Second Session of the First Parliament 1912 - South Africa Parliament (Cape Town Government Printer, 1912)
Debates of the House of Assembly of the Union of South Africa, as reported in the Cape Times. Debates / South Africa. Parliament. House of Assembly.
First Parliament, First Session, 1910/11-Fourth Session, 1914.
Keywords: Union of South Africa; Second Session - First Parliament; January to June 1912; JC044648; Debates